2022
DOI: 10.1055/s-0042-1748856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support Stewardship: Best Practices and Techniques to Monitor and Improve Interruptive Alerts

Abstract: Interruptive clinical decision support systems, both within and outside of electronic health records, are a resource that should be used sparingly and monitored closely. Excessive use of interruptive alerting can quickly lead to alert fatigue and decreased effectiveness and ignoring of alerts. In this review, we discuss the evidence for effective alert stewardship as well as practices and methods we have found useful to assess interruptive alert burden, reduce excessive firings, optimize alert effectiveness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Prior studies have shown that interruptive alerts are frequently disabled 37,38 due to inappropriate alert triggering, poor usability, or poor fit with the workflow, 39 with recommendation to avoid using interruptive alerts for nonemergent CDSS. 40,41 There is some evidence that interruptive alerts do cause more change in provider behavior than noninterruptive alerts, 39 giving credence to the idea that a noninterruptive IADx would commonly be ignored. 42 Provider preference may partly be explained by the fact that users were only offered the options of either an interruptive or noninterruptive BPA.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that interruptive alerts are frequently disabled 37,38 due to inappropriate alert triggering, poor usability, or poor fit with the workflow, 39 with recommendation to avoid using interruptive alerts for nonemergent CDSS. 40,41 There is some evidence that interruptive alerts do cause more change in provider behavior than noninterruptive alerts, 39 giving credence to the idea that a noninterruptive IADx would commonly be ignored. 42 Provider preference may partly be explained by the fact that users were only offered the options of either an interruptive or noninterruptive BPA.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the progress in NLP has focused on information retrieval and extraction [32]; however, the application of these methods at scale with a combination of software developers and operations remains challenging at health care institutions. The role of NLP in BPAs has been limited to date, and prior BPAs have used existing technologies embedded into the EHR [33]. Similar to prior motivations for BPAs delivered to bedside clinicians [34], our intention was to support and enhance decision-making at the beside with a recommendation for an Addiction Medicine consult in patients who may otherwise not receive it or have it delayed, similar to another NLP-driven BPA [17].…”
Section: Principal Findingsmentioning
confidence: 99%
“…In this study, psuedo-randomized testing is used to compare an experimental alert to the control of no alert. We see great potential for this methodology to support clinical decision support governance 29,30 -such trials can be used in future quality improvement projects to ensure that ineffective alerts are not perpetuated in the EHR by testing proposed interventions against a control 31 , particularly when multiple interventions are being trialed simultaneously Limitations of the EHR software make it difficult to conduct a truly randomized study without customization or use of a third-party application. In quality improvement or more operationally focused projects, it may be infeasible to dedicate the resources required to set up such an evaluation.…”
Section: The Use Of Pseudo-randomized Testing In Quality Improvementmentioning
confidence: 99%